Experience Realized in Edweek.org by a Black Student: an Appraisal Analysis of the Attitudinal Perspective - Fatwassani, Rezza (Educalingua Journal, 2023)
The purpose of this research is to describe the message expressed by a black American student as contained in the Edweek portal which was published in 2020. Specifically, the research tried to identify the language choice of the published text. The research focused on the attitudinal perspective of the appraisal system. The identification includes the aspect of affect, judgment, and appreciation. As the data collection, a text about Almaw's experience "This is My Everything" was chosen for further analysis. The research showed that the positive attitudinal lexis was equaled with the negative one. When the data were calculated in detail, the percentage of effect was 34%, judgment 58%, and appreciation 8%. The presence of equal data showed that there were mixed feelings expressed by a student when she shared her experience of racial abuse.